Kenya Apparel and Textile Industry : Diagnosis, Strategy and Action Plan - World Bank Group; Global Development Solutions (World Bank, Washington, DC, 2015)
Kenya’s textile and apparel sector has the potential to play a key role in anchoring the country’s deeper movement into middle income status and in serving as a source of gainful employment for its fast growing, young population. As a manufactured good, it offers opportunities for increased value capture and streamlined trade logistics and for the building of skills and experience from the factory floor to management level. Based on these foundations, it therefore serves as a potential gateway to other manufactured goods, offering opportunities for Kenya to capture an increasing share of global trade and to advance economic diversification. The report is structured as follows: chapter two describes global and regional market trends in textile and apparel. Chapter three reviews the evolution, growth, and performance of the apparel sector in Kenya and then analyzes the sector in terms of markets, products, and stakeholders. Chapter four focuses on Kenya’s performance in terms of relevant macro indicators and highlights the critical constraints faced by apparel manufacturers and exporters in Kenya. Chapter five concludes with recommendations. Where possible, chapters end with a summary of key points and conclusions.